Wood between pleasantness and perishability. Experimentations on bathing services - Felice Ragazzo; Teresa Villani (Agathón)
Temporary buildings are usually meant for emergency situations, however, design of temporary facilities is a paradigm used also for leisure activities, such as seasonal tourism. In this context, the paper presents a design experimentation performed on small, prefabricated facilities, all wooden, intended for bathing services. The aim is twofold: showing their expressive potential and introducing innovations in components and connections, while considering the perishability of wood, with a view of reusing them. The experimentation included a design integrated with computerized production systems, and the definition of a database – digitally implementable – of components and jointing modes.